Association of Angiotensin I Converting Enzyme Insertion/287 bp Deletion Polymorphisms and Proliferative Prostatic Diseases among Lebanese Men. (7th February 2020) - El Ezzi, Asmahan A.; Clawson, Jordan M.; El-Saidi, Mohammed A.; Zaidan, Wissam R.; Kovash, Abigail; Orellana, Jeremy; Thornock, AnnaKarina; Kuddus, Ruhul H.
Abstract : Background . Angiotensin I converting enzyme (ACE) insertion (I) and 287 bp Alu repeat DNA fragment deletion (D) polymorphisms have been indicated in various cancers. Here, we investigated I/D polymorphisms in prostate cancer (PCa) and benign prostate hyperplasia (BPH) among Lebanese men. Methods . Blood DNA extracted from 69 control subjects, 69 subjects with clinically confirmed PCa, and 69 subjects with clinical BPH, all the subjects were aged 50 years or older, was subjected to the polymerase chain reaction. The PCR products were resolved in polyacrylamide gels to determine II, ID, and DD genotypes. The odds ratios (OR), 95% confidence intervals (CI), and p values of the allele frequencies and genotype ratios were calculated for establishing possible association of the alleles and/or genotypes and PCa and/or BPH. Results . The proportions of II, ID, and DD genotypes were significantly different from Hardy–Weinberg equilibrium for BPH and PCa groups (but not the control group), mostly due to overabundance of the ID genotypes. There was no significant difference in the I and D allele frequencies between the control groups and the affected groups. The ratio of (DD + ID)/II is significantly lower among the control group compared to the BPH group (RR = 8.92, p = 0.042 ), and the ratio of ID/(DD + II) is significantly lower among the control group compared to the affected groups (RR = 1.99, p = 0.021 ). Conclusions . Our data indicate that the D allele of the I/D polymorphisms of the ACE gene is associated with increased risk of BPH, and the ID genotype is a risk factor for both BPH and PCa among Lebanese males.